1965
DOI: 10.1002/app.1965.070090603
|View full text |Cite
|
Sign up to set email alerts
|

Heptane‐soluble material from atactic polypropylene. I. Fractionation and characterization of fractions

Abstract: A sample of commercial atactic polypropylene was extracted with ether and the residue extracted with boiling n-heptane. S i fractions of the heptane-soluble material, which is very similar to that obtained by heptane extraction of isotactic polypropylene, were obtained by stepwise addition of acetone to a solution in cyclohexane. Densities, melting points, and x-ray photographs of the fractions and the unfractionated material were obtained and infrared absorption spectra used to estimate tacticity. Molecular w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1966
1966
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…[30] It has to be noted that the aPP that is reported to be miscible with iPP is often obtained as the heptane-soluble fraction of iPP, which also contains isotactic sequences. [33] Additionally, it is difficult to study the miscibility of iPP/aPP blends, since the blend components possess similar physical properties, such as electron density, scattering length density, refractive index, and T g . Figure 5 compares the influence of the type of rubber on the morphology of iPP/rubber blends containing 50 wt.-% of rubber, where the dark regions represent the rubber phase and the light regions the iPP phase.…”
Section: Compatibility Of Ipp/app-co-enb Blendsmentioning
confidence: 99%
“…[30] It has to be noted that the aPP that is reported to be miscible with iPP is often obtained as the heptane-soluble fraction of iPP, which also contains isotactic sequences. [33] Additionally, it is difficult to study the miscibility of iPP/aPP blends, since the blend components possess similar physical properties, such as electron density, scattering length density, refractive index, and T g . Figure 5 compares the influence of the type of rubber on the morphology of iPP/rubber blends containing 50 wt.-% of rubber, where the dark regions represent the rubber phase and the light regions the iPP phase.…”
Section: Compatibility Of Ipp/app-co-enb Blendsmentioning
confidence: 99%
“…Hawkins and Smith (2) found a separation in polyethylene which occurred on the basis of short-chain branching frequency; Wija et al (3) found the column technique to be sensitive to crystallinity as well as molecular weight in the fractionation of polypropylene when the elution temperature was kept below the melting point of the polymer. Natta and several other workers (7)(8)(9)(10) reported the use of a series of two extraction steps to obtain three fractions for the characterization of polypropylene. The most refined experiments using different solvents of increasing boiling points to achieve fractionation of polypropylene on the basis of stereoregularity were recently reported by Nakajima and Fujiwara ( 1 1 ) and by Yamaguchi et al (12).…”
Section: Discussionmentioning
confidence: 99%
“…(1) in the form of product of molar fraction of solvent in solution drop m(=n(te)/no(te)+1}) by its activity. That is, (6) Considering dilute solution in which m01, m and 0 can be approximated by the following equations, respectively.…”
Section: Introductionmentioning
confidence: 99%